2008
DOI: 10.1111/j.1532-7795.2008.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

High School Social Climate and Antisocial Behavior: A 10 Year Longitudinal and Multilevel Study

Abstract: A longitudinal and multilevel approach is used to examine the relationship between antisocial behavior during adolescence and high school social climate. The data are taken from a longitudinal study of 1,233 boys and girls who attended 217 public and private high schools. Students' disruptive behaviors were assessed yearly from 6 to 12 years of age. High school social climate was assessed by teachers, and students reported on their violent and nonviolent antisocial behavior while in high school. The multilevel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 59 publications
2
26
0
3
Order By: Relevance
“…There were no other significant associations of teacher well-being, burnout, or work environments with student risk-taking behaviors or symptoms. Although other studies have found little relationship between teacher work conditions and job satisfaction and student behavior problems [37], this is one of the first studies to show a link between teacher and student emotional well-being.…”
Section: Discussionmentioning
confidence: 97%
“…There were no other significant associations of teacher well-being, burnout, or work environments with student risk-taking behaviors or symptoms. Although other studies have found little relationship between teacher work conditions and job satisfaction and student behavior problems [37], this is one of the first studies to show a link between teacher and student emotional well-being.…”
Section: Discussionmentioning
confidence: 97%
“…Latent growth models describe time trajectories in terms of intercept (average over time) and slope (change over time) effects withinand between-school years. We focus primarily on slope effects, with the objective of providing a better empirical context for evaluating change mechanisms and their causal time scales (Collins & Graham, 2002;Gregson, 2011;LeBlanc, Swisher, Vitaro, & Tremblay, 2008).…”
Section: The Benefit Of Estimating Trajectories With Frequent Assessmmentioning
confidence: 99%
“…Dornbusch et al 2001;Vazsonyi and Pickering 2000); the effects of developmental disorders (because of ADHD, for instance) and individual characteristics such as gender and degree of impulsiveness (cf. LeBlanc et al 2008; Murteira Morgado and Da Luz ValeDias 2013); and school-related factors such as the influence of teacher involvement and the impact of inadequate classroom management (cf. Roorda et al 2011).…”
Section: Introductionmentioning
confidence: 99%